Top 100 most-cited articles on tau protein: a bibliometric analysis and evidence mapping - Chen, Zheping; Shan, Guoliang; Wang, Xinyue; Zuo, Yaqun; Song, Xinyu; Ma, Yufeng; Zhao, Xin; Jin, Yanwu (Frontiers in Neuroscience, 2024)
Background Tau, a microtubule-associated protein extensively distributed within the central nervous system (CNS), exhibits close associations with various neurodegenerative disorders. Here, we aimed to conduct a qualitative and quantitative bibliometric study of the top 100 most-cited publications on tau protein and reveal the current research hotspots and future perspectives. Methods The relevant literature was retrieved from the Web of Science Core Collection. CiteSpace (v6.2.R4) and VOSviewer (1.6.19) were adopted for bibliometric analysis with statistical and visual analysis. Results Citations per article ranged from 615 to 3,123, with a median number of 765.5 times. “Neuroscience” emerged as the most extensively researched subject in this field. The USA has emerged as the leading country, with a publication record (n = 65), total citations (n = 66,543), strong centrality (0.29), and extensive international collaborations. Harvard University (n = 11) and the University of California, San Francisco (n = 11) were the top two institutions in terms of publications. Neuron dominated with 13 articles in the 37 high-quality journals. M. Goedert from the MRC Laboratory of Molecular Biology was the most productive (n = 9) and top co-cited (n = 179) author. The most frequently studied keywords were Alzheimer’s disease (n = 38). Future research is anticipated to intensify its focus on the pathogenesis of various tau-related diseases, emphasizing the phosphorylation and structural alterations of tau protein, particularly in Alzheimer’s disease. Conclusion The pathogenesis of various tau-related diseases, including the phosphorylation and structural alterations of the tau protein, will be the primary focus of future research, with particular emphasis on Alzheimer’s disease as a central area of investigation.